Kajian Identiti Korporat Kedai Cenderamata D'kitar - Halim, H. (University Malaysia Sarawak, UNIMAS., 2007)
This research is to investigate the effectiveness and weakness of the corporate identity for a recycle product gift shop. Hence, creating a gift shop call "D'Kitar" that used recycle material as a souvenir.